2011
DOI: 10.7863/jum.2011.30.7.899
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing the Accuracy of 2‐Dimensional and Real‐time 3‐Dimensional Echocardiography for Assessment of Small Volumes, Areas, and Distances

Abstract: Objectives The aim of this study was to assess the validity, accuracy, and reproducibility of real‐time 3‐dimensional (3D) echocardiography for small distances, areas, and volumes. Methods Real‐time 3D echocardiography using matrix technology was performed in small calibrated tissue‐mimicking phantoms and compared with 2‐dimensional (2D) echocardiography. In a systematic variation of variables on data acquisition and analysis including different 3D workstations (manual disk summation versus semiautomatic borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Insights regarding the use of real-time 3D matrix transducers 15 and restrictions in spatiotemporal accuracy of RT3DE in pediatrics 16 were incorporated into the acquisition procedures. Measurement accuracy of the ultrasound scanners was validated using calibrated, static, tissue-mimicking phantoms 17 as well as moving phantoms. 16 In the core lab in Bonn, all data were reviewed and quantified.…”
Section: Study Design and Datamentioning
confidence: 99%
“…Insights regarding the use of real-time 3D matrix transducers 15 and restrictions in spatiotemporal accuracy of RT3DE in pediatrics 16 were incorporated into the acquisition procedures. Measurement accuracy of the ultrasound scanners was validated using calibrated, static, tissue-mimicking phantoms 17 as well as moving phantoms. 16 In the core lab in Bonn, all data were reviewed and quantified.…”
Section: Study Design and Datamentioning
confidence: 99%
“…Herberg et al 32 studied LV mass using in vitro models and magnetic resonance imaging, and their results indicated that real‐time 3D echocardiography was accurate for calculation of small distances and areas and was superior to 2D methods for calculation of small volumes with the size of the neonatal and infant heart (area: 2D, −7.0% ± 2.9%; 3D, −6.0% ± 2.8%; volume: 2D, −13.1% ± 4.5%; 3D, −6.7% ± 2.5%; P < .05). Real‐time 3D echocardiography showed significantly lower intraobserver and interobserver variability compared with 2D echocardiography (intraobserver coefficient of variation: 2D, 3.3%; 3D, 0.7%; interobserver coefficient of variation: 2D, 4.1%; 3D, 1.1%).…”
Section: Discussionmentioning
confidence: 99%
“…All of the images acquired from 4D echocardiography require manually modified tracing of endocardial and epicardial boundaries rather than the use of automated border detection because of the relatively low temporal resolution, and this process is time‐consuming. The gain, compression, and 3D workstation are still important factors for accurately analyzing the data, 32 so we hope that machines improve in resolution and the analysis software progresses in border‐tracking capabilities in the future. The frame rates used to acquire 4D images in this study were relatively low compared with current 2D modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RV volumes by 3DE were consistently smaller by 9%. Helberg 22 compared 3DE volumes to small, calibrated, tissue-mimicking phantoms. Although the authors concluded that 3DE was a reliable method for calculation of small distances, areas and volumes, 3D echo volume measurements were consistently smaller.…”
Section: Discussionmentioning
confidence: 99%